A case of Capgras syndrome and folie à duex in monozygotic twins. Issue 3 (4th May 2018) - Gbyl, Krzysztof; Balslev Jørgensen, Martin
ABSTRACT: Both Capgras syndrome and folie à deux (insanity of two) are rare and fascinating psychopathological syndromes. Their etiology and the nosological position remain unclear. We present a case of substance-induced Capgras syndrome emerging as folie à deux (insanity of two) in monozygotic twins with strongly overlapping life histories. Then, we discuss the etiology and the nosological position of these two conditions as well as their significance for understanding the concept of psychosis.